Examining Civil Law Remedies for Consumers Affected by Counterfeit Branded Goods in E-commerce Transactions - Ilham, Muhammad Azham; Kirana, Andi Rahmi Ainun (Al-Bayyinah, 2024)
This research aims to find out and explain the forms of legal protection for consumers and dispute resolution efforts related to the sale of counterfeit branded goods through online transactions in Indonesia. The research uses normative methods by reviewing library materials and secondary data and using legal material analysis techniques using a statutory approach. The research results show that consumer protection regarding the sale of counterfeit branded goods through online transactions in Indonesia refers to several statutory regulations, namely: Law Number 11 of 2008 concerning Information and Electronic Transactions, a form of protection for consumers, namely the requirement for business actors to provide correct and clear information regarding goods/services being bought and sold as well as guaranteeing the responsibility of business actors for losses and all legal consequences resulting from violations of obligations in electronic transactions. Based on Law Number 8 of 1999 concerning Consumer Protection, the form of legal protection for consumers is that in 2001 the Government established the National Consumer Protection Agency which then formed the Consumer Dispute Resolution Agency at the regional level. Based on Law Number 20 of 2016 concerning Brands and Geographical Indications, a form of consumer protection is the threat of criminal penalties for business actors who counterfeit brands or buy and sell products resulting from criminal acts. Consumer dispute resolution can be reached through 3 routes, namely peaceful resolution by the parties to the dispute without involving the court or a neutral third party, and settlement through the court. and Out-of-court settlement through BPSK.